YOUTH ENTREPRENEURSHIP AND RURAL ECONOMIC TRANSFORMATION IN DEVELOPING COUNTRIES - Risanty Marisca (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
Youth entrepreneurship is increasingly recognized as a strategic instrument for driving rural economic transformation in developing countries. Young people's involvement in entrepreneurial activities not only contributes to job creation and increased community incomes but also encourages innovation, economic diversification, and strengthened rural competitiveness. This study aims to analyze and synthesize previous research findings on the role of youth entrepreneurship in rural economic transformation in developing countries through a systematic literature review approach. The research method employed a literature review, examining various relevant scientific articles from reputable international and national journals. The study's results indicate that youth entrepreneurship significantly contributes to increasing local economic productivity, reducing unemployment and youth labor migration to urban areas, and accelerating the adoption of technology and innovation in the rural sector. Furthermore, the success of rural economic transformation is strongly influenced by government policy support, access to entrepreneurship education, strengthening the business ecosystem, and utilizing digital technology. This study confirms that youth entrepreneurship development can be an effective development strategy for creating inclusive and sustainable rural economic growth in developing countries.